Ternary organic–inorganic nanostructured hybrid materials by simultaneous twin polymerization. Issue 31 (25th July 2016) - Weißhuhn, J.; Mark, T.; Martin, M.; Müller, P.; Seifert, A.; Spange, S.
Abstract : The acid and base catalyzed simultaneous twin polymerization to produce ternary organic–inorganic nanostructured hybrid materials consisting of a cross-linked phenolic resin, silica and a disubstituted polysiloxane. Abstract : The acid and base catalyzed simultaneous twin polymerization (STP) of various 2, 2′-disubstituted 4 H -1, 3, 2-benzodioxasiline derivatives2a–d with 2, 2′-spirobi[4 H -1, 3, 2-benzodioxasiline] (1 ) are presented in this paper. The products are nanostructured ternary organic–inorganic hybrid materials consisting of a cross-linked organic polymer, silica and a disubstituted polysiloxane. It can be demonstrated whether and in which extent the copolymerization of the two inorganic fragments of1 and2 takes place among the STP and how the molar ratio of the two components determines the structure formation of the resulting hybrid material. Steric and electronic effects of the substituents at the silicon center of2 on the molecular structure formation and the morphology of the resulting hybrid material were investigated by means of solid state CP MAS 29 Si and 13 C NMR spectroscopy as well as high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM). The mechanical properties (hardness and Young's modulus) of the hybrid materials were analyzed by means of nanoindentation measurements.